1992
DOI: 10.1111/j.1476-5381.1992.tb09088.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of certain enantiomeric cannabinoids in the mouse vas deferens and the myenteric plexus preparation of guinea‐pig small intestine

Abstract: 1 The psychoactive cannabinoids (-)-A9-tetrahydrocannabinol ((-)-A9-THC) and the 1,l-dimethylheptyl homologue of (-)-11-hydroxy-A8-tetrahydrocannabinol ((-)-DMH) both inhibited electricallyevoked contractions of the mouse isolated vas deferens and the myenteric plexus-longitudinal muscle preparation of the guinea-pig small intestine. 2 Concentrations of (-)-A9-THC and (-)-DMH that decreased twitch heights by 50% were 6.3 and 0.15nM respectively in the mouse vas deferens and 60nM and 1.4nM respectively in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 17 publications
2
84
0
Order By: Relevance
“…We speculate that the high sensitivity of THC-mediated inhibition of synaptic transmission to firing frequency contributes to the variable effects reported for this drug in in vitro models. The only experiments to describe THC-mediated inhibition of synaptic transmission were performed at a stimulus rate of 0.1 Hz or less (Pertwee et al, 1996;Shen and Thayer, 1999;Azad et al, 2008) or used intermittent burst-type stimulus protocols with prolonged interstimulus intervals (Pertwee et al, 1992). It is noteworthy that a partial agonist at 5-hydroxytryptamine-3 receptors was shown previously to display a frequency-dependent reduction in the efficacy for inhibition of neurotransmitter release (Van der Vliet et al, 1988), suggesting that a general property of presynaptic inhibition produced by agonists of low intrinsic activity may be an especially high sensitivity to firing rate.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the high sensitivity of THC-mediated inhibition of synaptic transmission to firing frequency contributes to the variable effects reported for this drug in in vitro models. The only experiments to describe THC-mediated inhibition of synaptic transmission were performed at a stimulus rate of 0.1 Hz or less (Pertwee et al, 1996;Shen and Thayer, 1999;Azad et al, 2008) or used intermittent burst-type stimulus protocols with prolonged interstimulus intervals (Pertwee et al, 1992). It is noteworthy that a partial agonist at 5-hydroxytryptamine-3 receptors was shown previously to display a frequency-dependent reduction in the efficacy for inhibition of neurotransmitter release (Van der Vliet et al, 1988), suggesting that a general property of presynaptic inhibition produced by agonists of low intrinsic activity may be an especially high sensitivity to firing rate.…”
Section: Discussionmentioning
confidence: 99%
“…Each cohort was then further subdivided into three treatment groups receiving vehicle (1% Tween 80 in saline), 0.01 mg/kg THC, or 1.0 mg/kg THC (Sigma, UK). THC was prepared according to a previously published method (Pertwee et al, 1992). To permit counterbalancing in the behavioral task, an n ¼ 12 per treatment group was employed for behavior-positive animals, but, to reduce animal use, an n ¼ 8 per treatment group was employed in the behavior-negative animals, which were paired as far as group numbers permitted with behavior-positive animals receiving the same drug treatment.…”
Section: Drug Administrationmentioning
confidence: 99%
“…Cumulative concentration-response curves were constructed to the cannabinoid ligands with a 20 or 30 min dosing interval on tissues stimulated with 0.05 or 0.1 and 30 Hz respectively. Only one concentration-response curve was constructed per tissue as previous studies have shown that cannabinoids cannot be washed from the tissue by replenishing the bath with drug-free Krebs-Henseleit solution (Pertwee et al, 1992). When competition studies were performed, the cannabinoid receptor antagonists/inverse agonists were administered 30 min prior to the addition of the cannabinoid receptor agonists.…”
Section: Efs Experimentsmentioning
confidence: 99%